2016
DOI: 10.2337/dc16-0985
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Drug Utilization, Glycemic Control, and Rates of Severe Hypoglycemia, 2006–2013

Abstract: OBJECTIVETo examine temporal trends in utilization of glucose-lowering medications, glycemic control, and rate of severe hypoglycemia among patients with type 2 diabetes (T2DM).RESEARCH DESIGN AND METHODSUsing claims data from 1.66 million privately insured and Medicare Advantage patients with T2DM from 2006 to 2013, we estimated the annual 1) age- and sex-standardized proportion of patients who filled each class of agents; 2) age-, sex-, race-, and region-standardized proportion with hemoglobin A1c (HbA1c) <6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
226
4
17

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 273 publications
(266 citation statements)
references
References 39 publications
(51 reference statements)
19
226
4
17
Order By: Relevance
“…Rising trends in severe hypoglycaemia (resulting in emergency department visit or hospital admissions) have been reported in recent years for several high-SDI countries (USA, Canada, Japan, England) [14][15][16][17][18]. Most of these studies revealed a peak (2007 in the USA [14], 2006 in Canada and 2010 in Japan and England) followed by more stable trends.…”
Section: Discussionmentioning
confidence: 99%
“…Rising trends in severe hypoglycaemia (resulting in emergency department visit or hospital admissions) have been reported in recent years for several high-SDI countries (USA, Canada, Japan, England) [14][15][16][17][18]. Most of these studies revealed a peak (2007 in the USA [14], 2006 in Canada and 2010 in Japan and England) followed by more stable trends.…”
Section: Discussionmentioning
confidence: 99%
“…If both categories were used in tandem, as some have proposed, the combined costs could easily exceed the total expenditures for all retail prescription drugs in the U.S. as of 2014 (33)! Our group recently reported that while spending on diabetes medications has increased dramatically over the past decade, the mean HbA 1c and rates of hypoglycemia have not changed appreciably (12). These data suggest, at the very least, that the value of diabetes therapy must be carefully considered, especially if any major changes in traditional strategies are being contemplated.…”
mentioning
confidence: 97%
“…This body of evidence, along with metformin's low cost and general good tolerability, catapulted the drug in less than a decade to be the most commonly used oral antihyperglycemic agent in the U.S. (12). Most treatment guidelines, including those from the American Diabetes Association/European Association for the Study of Diabetes (13) and the International Diabetes Federation (14), suggest metformin be used as the first-line therapy after diet and exercise, barring any prevailing contraindications.…”
mentioning
confidence: 99%
“…It has been shown in rats that the systemic injection of insulin induces body growth [30, 33]. Furthermore, in vitro studies have demonstrated a stimulatory effect of insulin on chondrocyte proliferation [34-37] and variable effects on chondrocyte differentiation [35-38]. …”
Section: Systemic Factors In Malnutrition and Cu Growthmentioning
confidence: 99%